Methоd of rigging parameters calculation for midwater trawls - V. I. Gabruk; V. V. Kudakaev; L. A. Gabruk; A. N. Boitsov (Известия ТИНРО, 2018)
The rigging parameters calculation for midwater trawls are discussed with description of numerical model for calculating the parameters of trawl boards, hydrodynamic kites, and dispersed and concentrated weights which provide the designed values of horizontal and vertical opening of the trawl mouth. A distinctive feature of the proposed technique is a systematic approach: the trawl, trawl boards, and wires are considered as a joint complex.